Assessing food attributes and marketing services of private restaurants on the campus of University of Abomey-Calavi, Benin - Honfoga, Barthelemy G.; OHANETE, Pascal; TEVI, Charles D.; SEDEGNAN, Christelle O.; OGOUNCHI, Max-Régis (My University, 2019)
In Benin Republic (West Africa), the public student restaurant of the University of Abomey-Calavi is being criticized for its irregular and poor service. Therefore, private restaurants have settled on the campus streets to fill the gap. Which food attributes and marketing services do students value most? How do those restaurants compare with the Agro Maquis reference restaurant, which presumably offers modern catering services? The study aims to reveal food marketing services, as critical drivers of food demand in a restaurant. Principal component analysis was carried out to identify types of private restaurants that have settled on the streets of the campus. This was done based on 13 marketing service attributes. The set of restaurants with the prevailing profile was tested for conformity with the reference one. 60% of the private restaurants comply well with cleanness and 70% with attractiveness/prettiness of the place. Also, 90% of the private restaurants addressed the time-saving need of consumers in a satisfactory manner and 60% were found efficient in terms of hygiene. Three main groups of restaurants were revealed. The one mostly represented is the one that takes into account: hygiene, seller and food presentation and packaging, guest care quality, diversity of services and service time. The conformity test shows that the dominant restaurants in the campus streets compare quite well with the Agro-maquis restaurant for most product attributes and marketing services. Outsourcing of catering service to qualified private restaurants in public universities should be implemented, based on track records of attractive marketing services.
Keywords: Food demand; food attributes; marketing services; private restaurants; students; Benin